Medical attendance requirements of high performance athletes - Porcar, C.; Guerra, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Nowadays, to prevent injuries, it is important to know which kinds of injuries are more frequent. Some research has been done with an American high school population (Darrow, C J., Collins, C L., Yard, E E., Comstock, D., 2009). Through medical visits, we have studied athletes belonging to an Olympic Training Center and their epidemiologic characteristics to know the requirements for a medical attendance. Methods: Informatics Clinical histories of medical attendance were obtained and analyzed determining the number of visits done by the physician in charge of these athletes, as well as the variables associated to these visits. 16925 visits were analyzed during 45 months, in 16 Olympic sports. Variables were the following: Acute disease, Chronic disease, Chronic injury, Acute Injury, Recidivated injury, Sequel of injury, Injury`s circumstances (training, competition, non sportive), Topography of injury, Tissue structure damaged and Kind of injury. Results: Respiratory Diseases were the most frequent (52 % of the total number of medical visits). Headache was the second more frequent (12 %), Digestive system problems (9 %), dermatological diseases (12 %) and ORL (8 %). In relation to muscle-skeletal system, 90 % of all the injuries appeared during training. Acute were the most frequent (75 %) and only an 18 % were chronic injuries. In relation to affected tissue, the muscle was the most affected (27 %), followed by bone (16 %), tendon (13 %) and ligament (12 %). The most injured sports were tennis and gymnastic (16% each of them), track and field (12 %) and swimming and Tae-Kwon-Do (12 % each of them). Topography of injury showed that knee (17%), ankle (12%), foot (11%) and low back (10%) were the most frequent. Discussion: High performance athletes present peculiar epidemiologic characteristics (Spence , L. ,2007; Alonso, J M., Tscholl, P M.,2010) that need to be studied to optimized the health service that they receive. More research is needed to determine the characteristics that differ from a general population as well to determine the kind of injury related to the kind of sport (Hootman, J M., Dick, R., Agel, J. ,2007).